PERBEDAAN PENGARUH METODE PEMBELAJARAN DAN KOORDINASI MATA TANGAN TERHADAP PENINGKATAN KETEPATAN PUKULAN FOREHAND DRIVE PADA PERMAINAN TENIS MEJA SISWA SMA NEGERI 9 MAKASSAR - Munandar, Wahyu; Mahyuddin, Reza (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2018)
This research aimed to know 1) the difference of influence between massed practice learning methods and distributed practice towards increasing the accuracy of forehand drive blows in table tennis games, 2) The difference in increasing the accuracy of the forehand drive between those who have eye coordination - high and low hands, 3) Effect of interaction between learning methods and eye-hand coordination on increasing the accuracy of the forehand drive. This research was conducted by using design experimental method with a 2x2 factorial. The research was at SMA Negeri 9 Makassar. The samples in this research were 40 students and the populations were 78 students. The sample technique used purposive random sampling. The research variable consisted of two variables such as: manipulative variable (learning method of massed practice and distributed practice) and Attributive variable such as: High and low hand eye coordination, and the dependent variable is the accuracy of the forehand drive. The data collection technique used test and assessment namely: Hand eye coordination test using a tennis ball catch test and the accuracy of the forehand drive using the forehand drive placement test. The data analysis technique used SPSS 16.00 with significance level α = 0,05. The output of this research is in the form of information on the comparison of the more significant effects between the learning method and hand eye coordination on the improvement of the accuracy of the forehand drive in the table tennis game of SMA Negeri 9 Makassar